Analisis Faktor Yang Mempengaruhi Ketepatan Masa Studi Mahasiswa Program Studi Farmasi UIN Maulana Malik Ibrahim Malang - Hakim, Abdul; Indrawijaya, Yen Yen Ari; Yuwono, Yuwono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The 70% punctuality of graduating students is one of the quality targets of the Faculty of Medicine and Health Sciences UIN Maulana Malik Ibrahim Malang and is one of the assessment points in the LAM-PTkes accreditation. While the punctuality of graduation from the Pharmacy department FKIK UIN Malang was 20% for the 2013 class, 17% for the 2014 batch, 14% for the 2015 batch and 66% for the 2016 batch. does not meet the FKIK quality standards. This study was conducted to identify the factors that affect the punctuality of graduation for Pharmacy students so that it can help the Pharmacy department to improve the punctuality of graduation. The design of this research is an observational study that is cross-sectional. The results of this study are that there is no significant relationship between motivation and timeliness of graduation for students of the pharmaceutical study program at UIN Malang, there is no significant relationship between interest and timeliness of graduation for students of Pharmacy department UIN Malang, there is no significant relationship between intelligence There is no significant relationship between spiritual intelligence and the punctuality of graduating pharmacy study students at UIN Malang and there is no significant relationship between the scientific field and the punctuality of graduating Pharmacy study program students at UIN Malang. In conclusion, none of the factors studied had a significant relationship with the punctuality of graduating students from the pharmacy department at UIN Maulana Malik Ibrahim Malang.Keywords: punctuality of graduation, pharmacy department